Case report: A rare case of immunotherapy induced isolated left CN VI palsy in a patient with unresectable melanoma - Low, Samantha Su Ping; El-Shakankery, Karim; Brown, Ewan; Christie, Alan; McCormack, Sally; Stares, Mark (Frontiers in Oncology, 2024)
Introduction: Immune checkpoint inhibitors are the mainstay of treatment in patients with unresectable or metastatic melanoma. Combination immunotherapy with ipilimumab and nivolumab has shown to improve survival outcomes as compared to single agent immunotherapy in these patients. Neurological immune-related adverse effects (irAEs) are uncommon and cranial nerve palsies are seen even more infrequently.Case Presentation: A 66-year-old woman with a background of metastatic, unresectable melanoma with supraclavicular and axillary lymph nodal involvement presented with a headache, photophobia and diplopia 3 weeks after her first cycle of ipilimumab and nivolumab. She was subsequently diagnosed with a left-sided cranial nerve VI palsy and treated with high dose oral steroids and steroid eye drops, with complete resolution of symptoms. She also experienced Grade 3 dermatitis requiring topical steroids, Grade 2 hypothyroidism and vitiligo. She continues to have an excellent clinical and radiological response, despite further immunotherapy being suspended.This is the first reported UK case of immunotherapy-induced isolated cranial nerve VI palsy. Multiple irAEs are more common with combination immunotherapy and its occurrence is associated with more favourable outcomes in melanoma. Immunotherapy continues to revolutionise oncological care, but clinicians must be cognizant of unpredictable irAEs, which may require prompt assessment and intervention.